Multimodal biometrics recognition for newborns - Tiwari S.; Singh S.K. (My University, 2025)
Identification of newborns at birth is a critical issue for hospitals, birthing centers, and other institutions where multiple births occur. With approximately 300,000 infants born worldwide each day, a large hospital may experience over one hundred new births every day. Correct identification of infants is essential to ensure that each mother travels home with her own child. Mixing, abduction, and illegal adoption of newborns is a global problem, and the research done to solve this problem is minimal. In this chapter, the authors present a multimodal biometric framework for the recognition of newborns. © 2014, IGI Global.